Conexivisphaera calida gen. nov., sp. nov., a thermophilic sulfur- and iron-reducing archaeon, and proposal of Conexivisphaeraceae fam. nov., Conexivisphaerales ord. nov., and Conexivisphaeria class. nov. in the phylum Thaumarchaeota. Issue 1 (9th January 2021) - Kato, Shingo; Ohnishi, Masafumi; Nagamori, Mai; Yuki, Masahiro; Takashina, Tomonori; Ohkuma, Moriya; Itoh, Takashi
Abstract : A thermoacidophilic, anaerobic, and iron- and sulfur-reducing archaeon, strain NAS-02 T, was isolated from a terrestrial hot spring in Japan, as previously reported. This organism is the first non-ammonia-oxidizing isolate in the phylum Thaumarchaeota . Here, we propose Conexivisphaera calida gen. nov., sp. nov. to accommodate this strain. The type strain of the type species is NAS-02 T (=JCM 31663 T =DSM 105898 T ). The values of 16S rRNA gene similarity and average amino acid identity between NAS-02 T and its closest relatives are <86 and <42 %, respectively. Based on the phylogeny and physiology, we propose the family Conexivisphaeraceae fam. nov., the order Conexivisphaerales ord. nov. and the class Conexivisphaeria class. nov. to accommodate the novel genus.